2016
DOI: 10.1007/s40858-016-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of lesion mimic trait with spot blotch resistance in wheat

Abstract: Lesion mimic creates necrosis in the leaf tissue and promotes the growth of necrotrophic/hemibiotrophic pathogens. The presence of lesion mimic locus and their effect on spot blotch disease, days to heading, black point index and thousand kernel weight of wheat were investigated in parents Sujata, Avocet-YRA and their 146 recombinant inbred lines (RILs). The study conducted during two cropping seasons showed that some lines with higher expression of lesion mimic phenotypes exhibited significant increase in AUD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has also been shown that lesion mimic loci ( Lm/lm ) that are responsible for spontaneous formation of necrotic spots on leaves, and confer resistance to rusts, promote susceptibility to spot blotch. Therefore, the presence of these Lm loci in spot blotch resistant genotypes needs to be avoided in those wheat‐growing regions of South Asia, where rust is not yet a problem (Pandey et al ., ). In other places, where rusts and spot blotch are both a problem, deployment of Lm/lm for rust resistance also needs due care.…”
Section: Breeding For Spot Blotch Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…It has also been shown that lesion mimic loci ( Lm/lm ) that are responsible for spontaneous formation of necrotic spots on leaves, and confer resistance to rusts, promote susceptibility to spot blotch. Therefore, the presence of these Lm loci in spot blotch resistant genotypes needs to be avoided in those wheat‐growing regions of South Asia, where rust is not yet a problem (Pandey et al ., ). In other places, where rusts and spot blotch are both a problem, deployment of Lm/lm for rust resistance also needs due care.…”
Section: Breeding For Spot Blotch Resistancementioning
confidence: 97%
“…Indeed, Pandey et al . () suggested that tissue necrosis (the result of hypersensitivity) encourages the growth and reproduction of B. sorokiniana . It has actually been shown that in addition to HR, resistance is also provided by the epidermal cell walls, electrolyte leakage from infected tissue of the host and formation of papilla‐like cell wall apposition, laid down by the host at the site of attempted penetration by the fungus (Kumar et al ., ; Ibeagha et al ., ).…”
Section: Mechanism Of Spot Blotch Resistancementioning
confidence: 99%